What can biomarkers tell us about cognition in Parkinson's disease?. Issue 5 (15th April 2014) - Mollenhauer, Brit; Rochester, Lynn; Chen‐Plotkin, Alice; Brooks, David; Burn, David; Weintraub, Daniel; Robbins, Trevor
ABSTRACT Cognitive decline is common in Parkinson's disease (PD), even in the early motor stage, and this non‐motor feature impacts quality of life and prognosis tremendously. In this article, we discuss marker candidates for cognitive decline in PD from different angles, including functional and structural imaging techniques, biological fluid markers in cerebrospinal fluid, and blood genetic predictors, as well as gait as a surrogate marker of cognitive decline. Specifically, imaging‐based markers of cognitive impairment in PD include cortical atrophy, reduced cortical metabolism, loss of cortical cholinergic and frontal dopaminergic function, as well as an increased cortical amyloid load. Reduced β‐amyloid(1‐42) in cerebrospinal fluid and lower plasma levels of epidermal growth factor are predictors for cognitive decline in PD. In addition, genetic variation in the apolipoprotein E (APOE), catechol‐O‐methyltransferase (COMT), microtubule‐associated protein tau (MAPT), and glucocerebrosidase (GBA) genes may confer risk for cognitive impairment in PD; and gait disturbance may also indicate an increased risk for dementia. Other marker candidates have been proposed and are discussed. All of the current studies are hampered by gaps in our knowledge about the molecular causes of cognitive decline, which will have to be considered in future biomarker studies. © 2014 International Parkinson and Movement Disorder Society